Gastrointestinal helminthiasis and eimeriosis in grazing alpacas in two communal farms of Pasco, Peru and their relationship with body weight and body condition - Mason, Marine (2017)
The aim of this study was to study the relationship between gastrointestinal parasites with body weight and body condition in alpacas grazing in the Andean region of Pasco, Peru. Faecal samples from 160 alpacas in two communal farms were collected and analysed by the McMaster technique and faecal culture to determine the parasite load and parasite species. Due to the low prevalence of nematodes was decided to evaluate the relationship between Eimeria macusaniensis burden with the two productive parameters. The results showed a negative and significant correlation between parasite load and body weight (r2=0.8938) and non-significant correlation between parasite load and body condition (r2= 0.5747).